2020
DOI: 10.3390/ijerph17051591
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Rates in an Area with High Livestock Density: A Registry-Based Study Including Different Groups of Patients with Respiratory Health Problems

Abstract: There is continuing debate and public health concern regarding the previously confirmed association between high livestock density and human health. The primary aim of the current study is to assess the prevalence of respiratory and other health problems in a livestock dense area in the Netherlands, based on recent longitudinal health data and a large sample. Analyses are expanded with the investigation of different subgroups of patients with respiratory health problems and the inclusion of various chronic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…However, this study indicated that higher livestock units had a negative influence on self-perceived physical health. A recent study supported our results and concluded that a dense livestock area adversely affects human health [46]. On the other hand, different types of animals are linked with different zoonoses and risk factors for brucellosis [18].…”
Section: Discussionsupporting
confidence: 89%
“…However, this study indicated that higher livestock units had a negative influence on self-perceived physical health. A recent study supported our results and concluded that a dense livestock area adversely affects human health [46]. On the other hand, different types of animals are linked with different zoonoses and risk factors for brucellosis [18].…”
Section: Discussionsupporting
confidence: 89%
“…One limitation of EMR is that such data do not provide information on possible confounders such as smoking and socio-economic status, so no adjustment was possible. Data on other diseases that may be a risk factor for pneumonia, like chronic obstructive pulmonary disorder (COPD), are available in EMR data, but these were not included because possible interactions with such health outcomes were out of the scope of this study; such health outcomes have been studied separately [5, 28, 29]. Previous research on a smaller population that adjusted for these potential confounders and comorbidities found limited influence on the associations between pneumonia and proximity to goat farms [11].…”
Section: Discussionmentioning
confidence: 99%
“…The data provided by the above cited-studies [45][46][47][48] suggests that a link between excess COVID-19-related mortality and farming-related atmospheric pollutants is biologically plausible. The specific association we found between COVID-19-related mortality and NH3 might be explained by the hypothesis that atmospheric NH3 leads to the formation of alkaline aerosol which triggers a conformation change in the SARS-CoV-2 spike that facilitates fusion of the viral envelope with the plasma membrane of target cells [49].…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have reported associations between exposure to livestock farming and respiratory diseases. Thus, a Netherlands study found that people living in high livestock density areas had a significantly higher prevalence of pneumonia than those living in low density areas [45]. A German study [46] found that people exposed to higher levels of NH3 had poorer pulmonary health and were more likely to be sensitized to ubiquitous allergens, than persons with lower NH3 exposure.…”
Section: Discussionmentioning
confidence: 99%